Subjective expected utility theory without states of the world - Edi Karni (The Johns Hopkins University, Department of Economics, 2005)
This paper develops an axiomatic theory of decision making under uncertainty that dispenses with the state space. The results are subjective expected utility models with unique, action-dependent, subjective probabilities, and a utility function defined over wealth-effect pairs that is unique up to positive linear transformation.
Keywords: D81; 330; Subjective expected utility; states of the world; Erwartungsnutzen; Entscheidungstheorie; Prinzipal-Agent-Theorie; Theorie